IS THE EMPLOYMENT SITUATION IN INDONESIA FAVORABLE? IMPLEMENTATION OF VERHULST MODEL DIFFERENTIAL EQUATION - Fanny Novika (LPPM Universitas Bina Bangsa, 2023)
This research aims to calculate the limit number of workers and unemployment in each province of Indonesia which is estimated to use Carrying Capacity and calculate the employment growth rate of each province in Indonesia. This calculation will help to identify provinces in Indonesia where the growth rate of the working population is negative, the unemployment rate is positive. All of these calculations use the Verhulst Model Differential Equation. The data used in this research is secondary data obtained from the internet from the official website of the BPS-Statistics Indonesia regarding the Labor Force Situation in Indonesia from 2020-2023. The provinces with a lower working population growth rate, especially have negative value demands particular focus on labor absorption that are West Papua, Central Sulawesi that have high level warning status as well as Maluku and Bali that have medium level warning status. Besides the province with a greater unemployment population growth rate, especially has positive value demands particular focus on labor absorption that is Central Java that have medium level warning status